Analisis Karakteristik Kalsium Karbonat (CACO3) sebagai Filler pada Campuran Aspal Panas - Putra, Yudhistira Ananto; Hartatik, Nurani (Portal: Jurnal Teknik Sipil, 2024)
In the continuous effort to enhance the efficiency and sustainability of road pavement construction, research on alternative filler materials has become a primary focus. This study aims to analyze the feasibility of the characteristics of Calcium Carbonate (CaCO3) as a substitute filler in hot mix asphalt. Testing was conducted through sieve analysis, specific gravity testing, and sulfur and chloride content testing. The research adheres to the 2018 General Specifications of Bina Marga, SNI 0013-81, and ASTM C 618-05 regulations. The analysis results indicate that Calcium Carbonate (CaCO3) can be considered as a viable alternative filler material. Sieve analysis using two samples with an average percentage passing the No.200 sieve of 99.06% complies with the requirements of the 2018 General Specifications of Bina Marga, which stipulates a minimum value of 75% of the initial weight for filler sieve analysis. Specific gravity testing reveals an average value for calcium carbonate filler of 2.70 gr/cm3, meeting the SNI 0013-81 standard with a minimum value of 2.50 gr/cm3, making it suitable for use in hot mix asphalt. Sulfur and chloride content testing produces a Chloride (Cl) Content value of 0.004% using the Spectrophotometric method and a Sulfur (S) value of 0.01% using the Gravimetric method. Both values comply with ASTM C 618-05, which sets the limit for sulfur and chloride content at 0.05%. Therefore, Calcium Carbonate (CaCO3) can be considered a feasible alternative as a filler material in hot mix asphalt, based on the test results and compliance with applicable standards.